Biological characteristics of one Pteria sternapopulation (Bivalvia: Pteriidae) from Zorritos, Tumbes, Peru - Ordinola, Elmer (2013)
Between April and November 2011 was analyzed a population of Pteria sterna (Gould, 1851) which was attached to a sunken purse seine in Zorritos, Tumbes, Peru (3º40'30.7"S - 80°40'20.8"W). Individuals presented from 5 to 94 mm valve height. The average size increased towards the end of the assessment period. The size structure indicated the presence of recruits in most months evaluated, with highest in April and August. There were five age groups. The sex ratio was 1:1. The spawns were continuous, except in June, with highest in November. Valvar height-total weight relationship did not differ by sex. The growth of this species was negative allometric. Other relationships (potential: body weight-total weight, and linear: body weight-total weight and muscle weight-total weight) showed high correlations. Muscle performance accounted for 6.3% of the total weight.